1998
DOI: 10.1002/(sici)1522-7189(199802)6:1<27::aid-nt6>3.3.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stachybotrys chartarum atra conidia and isolated toxin on LungSurfactant production and homeostasis

Abstract: This study evaluated the effects of Stachybotrys chartarum conidia and a trichothecene, isosatratoxin-F, on choline incorporation into DSPC by fetal rabbit alveolar type II cells and on alveolar surfactant subtypes in mice. Exposure of fetal rabbit type II cells to S. chartarum conidia at concentrations of 10(3) to 10(6) conidia ml(-1) significantly depressed [3H] choline incorporation after 24 h of exposure. Exposure of the rabbit cells to 10(5) to 10(6) conidia ml(-1) also resulted in significantly depressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 28 publications
(48 reference statements)
1
18
0
Order By: Relevance
“…Early studies showed that surfactant production is up-regulated in type II alveolar cells exposed to pollutants (98,120,311). Subsequent work has shown that alveolar type II cells, macrophages, and surfactant production and composition are affected by exposure to fungal spores and their mycotoxins, including Cladosporium and Stachybotrys species (181,249,250,255,378; W. G. Sorenson, Proc. Int.…”
Section: Effects Of Stachybotrys In Indoor Air 155mentioning
confidence: 99%
“…Early studies showed that surfactant production is up-regulated in type II alveolar cells exposed to pollutants (98,120,311). Subsequent work has shown that alveolar type II cells, macrophages, and surfactant production and composition are affected by exposure to fungal spores and their mycotoxins, including Cladosporium and Stachybotrys species (181,249,250,255,378; W. G. Sorenson, Proc. Int.…”
Section: Effects Of Stachybotrys In Indoor Air 155mentioning
confidence: 99%
“…Each mouse used for the study was inoculated intratracheally with 50 µl of S. chartarum spores, (1.4 × 10 6 spores/ml in physiological saline = 75,000 spores/animal = 3,000 spores/g BW) (Mason et al, 1998). The mice were placed back into their cages immediately after instillation.…”
Section: Intratracheal Instillations In Vivo Mouse Modelmentioning
confidence: 99%
“…Schulz et al concluded that there is a health hazard due to toxic effects after the inhalation of high concentrations of spores from the filamentous fungi [20]. It has also been known for some time that toxins produced by Stachybotrys chartarum can accumulate to very high levels in the conidia and that spores laden with toxins can affect lung function [21,22,23]. However, the role that mycotoxins have in the manifestation of the aforementioned ailments is currently unknown, and studies aimed at mycotoxin inhalation exposure are lacking.…”
Section: Introductionmentioning
confidence: 99%